The representation of Irish affairs in La Gazette and in Nouvelles Ordinaires de Londres, 1649-1652 - Karine BIGAND (E-REA)
The monarchical crisis of the 1640s and the ensuing Wars of the Three Kingdoms in the British Isles were regularly reported and commented upon in France, notably in Théophraste Renaudot’s Gazette. Recent research has shown that its proximity with the Court and Mazarin’s government did not prevent the newspaper’s editor from constantly seeking news to feed its readers’ curiosity. The context in 1649-1652 was particularly newsworthy – as Charles I’s execution and the establishment of a new regime in England coincided with the beginning of the Fronde in France. As long as France refused to recognize the new Republic – until the end of 1652 – representing events going on across the Channel had a particular political impact. A lot of the reported news was from the last bastions of royalist resistance, Scotland and Ireland. From the summer of 1650, a new periodical, Nouvelles Ordinaires de Londres, was written in French in London and published on the continent, thereby promoting a different take on British news. The proximity of the Nouvelles Ordinaires de Londres’s editor to the Republican power meant that the publication sought to legitimize the new regime and assert its power on the continent. Using the example of Ireland, initially supported by France before the Republic defeated it, this article will shed light on the choice of news published and connections between the representation of Irish affairs in the two periodicals and the evolution of Franco-English relations.